Corneal epithelial thickness as a diagnostic tool in ophthalmology – a case series - Karolina Deja; Justyna Izdebska; Jerzy Szaflik (Klinika Oczna)
Following the introduction of a commercially available SD-OCT system in 2017, corneal epithelial mapping was incorporated into ophthalmology, particularly refractive surgery, as a valuable, highly diagnostic tool. In physiologically normal conditions, central epithelial thickness is 53-54 μm. Abnormal corneal epithelial thickness is observed in individuals with early keratoconus, in chronic contact lens wearers, and post corneal refractive surgery. In this paper, we present selected clinical cases in which corneal epithelial mapping performed with the Cirrus 5000 HD-OCT system (Zeiss) was used. The study group consisted of patients undergoing assessment of eligibility for refractive and cataract surgery or keratoconus treatment at the LASER Eye Microsurgery Centre in Warsaw. In the reported cases, corneal epithelial mapping contributed to modifying the diagnostic approach. In a patient with keratoconus, the characteristic ‘doughnut pattern’ was observed in the corneal epithelium. Identification of this symptom during the patient’s preoperative evaluation for refractive surgery prevented the irreversible iatrogenic complication of ectasia. A patient who reported a decline in visual acuity following SMILE surgery was diagnosed with an atypical epithelial healing pattern. The patient was advised to continue the prescribed treatment and was subjected to ongoing monitoring. At the follow-up visit, the patient reported an improvement in her visual acuity. A subsequent OCT examination showed normal pattern of epithelial distribution. Epithelial thickness can be a valuable parameter in the assessment of patient eligibility for refractive surgery. In addition, it may help determine the flap size and the depth of laser or keratome incision. This, in turn, contributes to optimal postoperative refractive outcomes.